Different modalities of entry in a large urban clinic in Uganda and impact on outcomes of patients assessing HIV care and treatment. Issue 2 (1st February 2017) - Castelnuovo, Barbara; Musomba, Rachel; Musaazi, Joseph; Kiragga, Agnes N.
ABSTRACT: In resource-limited settings, a number of patients do not receive continuous HIV care. In this analysis, we compared outcomes in patients who entered care by different modality of entry. This was a retrospective analysis of all patients started on antiretroviral treatment (ART) at a large urban center in Uganda from 2005 to 2012. Patients were categorized into three groups (1) Front door : started on ART without interruption during follow-up; (2) drop-out side door : restarted on ART after having an interruption >6 months and (3) transfer-in side door : transferred-in after being started on ART somewhere else. We compared characteristics at enrollment in the three groups and investigated the following outcomes: (1) retention in care (2) switch to second line. In the study period 11, 528 (87.2%) were enrolled through the front door, 1159 (8.7%) resumed ART after dropping out, while 527 (4%) patients were transferred in on ART. The three groups were generally comparable, although patients transferred in were sicker. A larger proportion of patients entered through the drop-out side door died or was lost to follow-up (37.3%), as compared to patients in the front door group (24.9%) and transferred-in side door group (17.7%). More patients in the front door group (32.1%) were transferred out during the follow-up. The highest probability of switching to second line was found in the transferred-in group. Patients who re-enter our program after dropping out are at higher risk of dropping out of care and often need to be switched to second-line ART. The high demand for second-line therapy among patients in transfer-in side door reflects failure in management of complicated patients who are usually require "up-transfer" to better treatment centers. In future understanding, the different modes of entry into HIV care will be key in reshaping the general cascade of HIV care.